Zinc drives vasorelaxation by acting in sensory nerves, endothelium and smooth muscle - Ashenafi H. Betrie (Nature Portfolio, 2021)
Metals such as calcium and potassium have long been known to regulate the diameter of arteries that control blood flow. Here, we report that zinc causes relaxation of blood vessels and reduces blood pressure by its coordinated action in sensory nerves, endothelium and smooth muscle cells.